Computer guided surgery in the maxillary esthetic zone - Jéssica Lemos GULINELLI; Thiago CALCAGNOTTO; Marcus Vinicius Satoro KASAYA; Caio Peres BELLATO; Eduardo Sanches GONÇALES; Pâmela Letícia dos SANTOS (Faculdade São Leopoldo Mandic, 2021)
ABSTRACT This clinical report describes the implant rehabilitation for the treatment of pathological roots resorption due to inadequate orthodontic movement in prosthetic space reduced by means of load and immediate implants, computer-guided surgery and use of the own tooth crown in a 21-year-old-patient. The atraumatic exodontics of the right and left upper lateral incisors was performed, and then immediate placement of osseointegrated implants using the computer guided surgery technique. The crown teeth itself was used in the immediate aesthetic and functional rehabilitation. Completion of the treatment resulted in a functional and aesthetic successful outcome and a 27 months follow-up presented uneventful. The procedures included in this complex rehabilitation treatment in the esthetic zone were appropriate and essential for the maintenance of the soft and hard tissues contour and thickness ensuring the excellence in rehabilitation.